DAMPAK PSIKOLOGIS PERNIKAHAN DINI BAGI PEREMPUAN - Fifin Dwi Purwaningtyas; Evi Ristanti; Yeni Lutfiatin Dewi Aisyah; Mochamad Choirudin (PSIKOWIPA (Psikologi Wijaya Putra), 2022)
Since East Java Province is responsible for 27.09 percent of the country's total, the author chose to conduct his studies there, namely in Jombang City, Ngusikan District, Manunggal Village. According to the author's research, women who get married at a young age tend to have slower psycholoical and physical maturation. Women who choose to marry before the traditional age of majority—between the ages of 19 and 20—are expected to have reached a higher level of maturity than their contemporaries. There will be emotional repercussions for the woman as a result of this. The author wanted to know more about "the psychological impact of early marriage for women," so she set out to do some investigating. Using observation, interview, and coding strategies on two subjects who meet the criteria for qualitative research. The findings demonstrated that women's mental health is negatively affected by marriage at a young age.